Acoustic spectroscopy of magnetic fluids based on transformer oil. (April 2016) - Kúdelčík, Jozef; Hardoň, Štefan; Bury, Peter; Kopčanský, Peter; Timko, Milan
The structural changes in transformer oil–based magnetic fluids with magnetite nanoparticles, FeO·Fe2 O3, of different diameters upon the effect of an external magnetic field were studied by acoustic spectroscopy. The corresponding changes of the acoustic wave attenuation as a function of magnetic field were measured. Over the linear increasing magnetic field, the interaction between the magnetic field and the magnetic moments of the nanoparticles led to the aggregation of magnetic nanoparticles and following chain or cluster formation. These structures enlarged with the magnetic field and this process had the influence on the value of the acoustic attenuation. The remarkable changes in the acoustic attenuation were also observed in the magnetic fluid subjected to a jumped magnetic field observed for a given time. After the back change of magnetic field to zero, the attenuation drastically decreases because the lifetime of big clusters is in this case small. The anisotropy of the acoustic attenuation in external magnetic field was measured and analyzed at various temperatures, and the cluster radius, the number density of the colloidal nanoparticles, and some other parameters of magnetic nanoparticles could be determined from experimental results.